Periapical tissue healing after post space preparation with or without use of a protection plug and root canal exposure to the oral environment. Study in dogs - Holland, Roberto [UNESP]; Manne, Luciana Noronha; Souza, Valdir de [UNESP]; Murata, Sueli Satomi; Dezan Junior, Eloi [UNESP] (FapUNIFESP (SciELO), 2007)
The purpose of this study was to evaluate the influence of coronal leakage on the healing of dogs' periapical tissues after root canal filling, post space preparation and protection or not with a temporary sealer plug. Forty root canals of dogs' teeth were instrumented and filled by the lateral condensation technique with gutta-percha points and Endomethasone or CRCS sealers. After post space preparation, the remaining filling material was protected or not with a plug of temporary Coltosol sealer and exposed to the oral environment for 90 days. Thereafter, the animals were sacrificed and the specimens were removed and prepared for histomorphological and histobacteriological analysis. The findings revealed 35% of microbial leakage in the groups without plugs and 15% of leakage in the groups with plugs. Statistical analysis showed that the use of a Coltosol plug improved significantly the histomorphological results regardless of the type of root canal sealer (p=0.05) and that CRCS and Endomethasone sealers showed similar results (p>0.05).
Keywords: Coronal leakage; Periapical repair; Post space preparation; Root canal sealer; Root canal therapy; Calcibiotic Root Canal Sealer; calcium hydroxide; calcium sulfate; Coltosol F; corticosteroid methanetriol mixture; dexamethasone; drug derivative; formaldehyde; gutta percha; hydrocortisone; protective agent; root canal filling material; thymol; unclassified drug; zinc oxide; zinc sulfate; animal; cementum; dentin; dog; drug combination; endodontics; Gram negative bacterium; Gram positive bacterium; instrumentation; isolation and purification; methodology; microbiology; pathology; periodontal ligament; periodontium; physiology; tooth crown; tooth disease; tooth pulp; tooth root; wound healing; Animals; Calcium Hydroxide; Calcium Sulfate; Dental Cementum; Dental Leakage; Dental Pulp; Dental Pulp Cavity; Dentin; Dexamethasone; Dogs; Drug Combinations; Formaldehyde; Gram-Negative Bacteria; Gram-Positive Bacteria; Gutta-Percha; Hydrocortisone; Periapical Tissue; Periodontal Ligament; Post and Core Technique; Protective Agents; Root Canal Filling Materials; Root Canal Obturation; Root Canal Preparation; Thymol; Tooth Apex; Wound Healing; Zinc Oxide; Zinc Sulfate